Frontend Website Implementation for Breast Cancer Classification System Using Machine Learning - Wardani , Shania; Wibowo, Suryo Adhi; Usman, Koredianto (eProceedings of Engineering, 2025)
Early detection of breast cancer is essential to improve patient survival rates. One way to be used for such detection is to develop a classification system based on genomic data, which can provide more accurate and efficient results. This study aims to design and implement a Streamlit-based website frontend, which functions as a breast cancer classification system interface using Machine Learning technology. This user interface is designed with ease of use and optimal user experience, allowing medical personnel to quickly access and understand the analysis results. The main features of this website include an educational dashboard about breast cancer, a simple and structured patient data input form, and predictive analysis results displayed in an interactive format and can be downloaded for further documentation purposes. Tests conducted on the front of this website show that the system response time to display the analysis results is no more than 5 minutes, making it an efficient solution in supporting medical decision-making. With an intuitive and easily accessible interface, this website makes it easy for medical personnel to perform breast cancer analysis faster and more accurately, supporting more effective early detection efforts. Keywords: Streamlit, User Interface, Breast Cancer, Website